A multilevel model of the help-seeking behaviors among adolescents with mental health problems - Zhao, Mei; Hu, Mi (Frontiers in Integrative Neuroscience, 2022)
Abstract Objective: Mental health problems are highly prevalent among adolescents yet the utilization of mental health services among such a population is very low. The current study was conducted to examine mental health problems and related help-seeking behaviors among a Chinese sample of adolescents. Methods: 3480 students were recruited from four middle and high schools in Changsha City, Hunan province, and completed an online questionnaire that assessed their general information, mental health problems including depression, anxiety, self-harm, and suicide ideation, as well as their help-seeking behaviors from both formal (including psychological teachers and mental health professionals) and informal sources (including family, friends, and teachers). Results: The participants had a prevalence of 13.7% for depression,11.5% for anxiety, 9.8% for self-harm, and 9.1% for suicide ideation. Although a high rate of help-seeking behaviors was observed (73.0%), most were concentrated in informal sources (99.3%), while only a small portion of participants resorted to formal sources (13.9%). Being female (OR: 1.45, 95% CI: 1.15-1.83), higher grade (OR: 1.32, 95% CI: 1.01-1.73), school mental health resources not available (OR: 1.39, 95% CI: 1.02-1.88), without suicide ideation (OR: 2.03, 95% CI: 1.42-2.90) were all associated with increased likelihood of formal help-seeking behaviors. On the other hand, complete middle school (OR: 0.36, 95% CI: 0.22-0.59), middle level of academic ranking (OR: 0.64, 95% CI: 0.42-0.97), higher father education levels (OR: 0.54-0.56, 95% CI: 0.33-0.90) were all associated with a decreased likelihood of formal help-seeking behaviors. Conclusion: Our results showed a higher prevalence of help-seeking behavior for emotional or psychological problems during the past year. Compared to the high rate of informal help-seeking behaviors, students showed a lower propensity to seek formal help for their mental health problems, which may be explained by individual-level, family-level, and school-level factors. Our findings provide important implications for the development and popularization of targeted, needs-based mental health promotion and education programs in the future.